Using a Single Internal Mammary Artery as Retrograde and Antegrade Flow for Bilateral Deep Inferior Epigastric Artery Perforator Reconstruction: A Case Report - Tyrell, Richard; Leong, Rachelle Y.; Sathyanarayana, Sandeep A.; Korn, Peter; Kadison, Alan S. (International Journal of Angiology, 2016)
Deep inferior epigastric artery perforator (DIEP) flaps have become an attractive option for autologous breast reconstruction. The internal mammary artery (IMA) is the usual artery of choice for reconstruction. Unfortunately, there are certain situations when the IMA may not be suitable for usage as in previous radiation or diminutive size. Several options have been documented, such as using the thoracodorsal vessels. In this case report, we report usage of the distal and proximal ends of a contralateral single mammary artery to supply antegrade and retrograde flow to bilateral DIEP flaps. With increasing complexity of patient populations, the use of alternate approaches to recipient vessel in DIEP reconstruction becomes essential for effective outcomes.
Keywords: DIEP; internal mammary artery; antegrade; retrograde; breast reconstruction